2014
DOI: 10.2527/jas.2014-7772
|View full text |Cite
|
Sign up to set email alerts
|

The requirement of GnRH at the beginning of the five-day CO-Synch + controlled internal drug release protocol in beef heifers1

Abstract: The objective of this study was to determine if the omission of GnRH at controlled internal drug release device (CIDR) insertion would impact pregnancy rates to timed AI (TAI) in beef heifers enrolled in a 5-d CO-Synch + CIDR protocol that used 1 PGF2α dose given at CIDR removal. Yearling beef heifers in Ohio in 2 consecutive breeding seasons (2011, n = 151, and 2012, n = 143; Angus × Simmental), Utah (2012, n = 265; Angus × Hereford), Idaho (2012, n = 127; Charolais), and Wyoming (2012, n = 137; Angus) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 19 publications
4
28
1
2
Order By: Relevance
“…In contrast, another study in yearling beef heifers showed that omission of the initial GnRH treatment in the modified 5-day Co-Synch þ CIDR protocol did not influence TAI pregnancy rate [19]. In both studies, a single dose of PGF 2a at CIDR removal resulted in adequate luteolysis and pregnancy rates regardless of whether or not the heifers received GnRH at CIDR insertion [18,19].…”
Section: Fig 2 Progesterone (P 4 ) Concentration (Ng/ml) At Initiatmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, another study in yearling beef heifers showed that omission of the initial GnRH treatment in the modified 5-day Co-Synch þ CIDR protocol did not influence TAI pregnancy rate [19]. In both studies, a single dose of PGF 2a at CIDR removal resulted in adequate luteolysis and pregnancy rates regardless of whether or not the heifers received GnRH at CIDR insertion [18,19].…”
Section: Fig 2 Progesterone (P 4 ) Concentration (Ng/ml) At Initiatmentioning
confidence: 90%
“…Interestingly, a recent study in dairy and beef heifers showed that GnRH administration at the time of CIDR insertion was beneficial in beef heifers but not in dairy heifers to improve pregnancy when using the modified 5-day Co-Synch þ CIDR protocol [18]. In contrast, another study in yearling beef heifers showed that omission of the initial GnRH treatment in the modified 5-day Co-Synch þ CIDR protocol did not influence TAI pregnancy rate [19]. In both studies, a single dose of PGF 2a at CIDR removal resulted in adequate luteolysis and pregnancy rates regardless of whether or not the heifers received GnRH at CIDR insertion [18,19].…”
Section: Fig 2 Progesterone (P 4 ) Concentration (Ng/ml) At Initiatmentioning
confidence: 92%
“…However, in beef heifers, the same contrast of treatments has mixed results. Cruppe et al (2014) reported similar pregnancy rates in beef heifers, while Kasimanickam et al (2014) reported that elimination of G1 resulted in decreased pregnancy rates in beef heifers when compared to the standard 5dCO. The inconsistent results, in beef heifers, leave an unanswered question as to the requirement of G1 within the 5dCO.…”
Section: Introductionmentioning
confidence: 93%
“…One way to increase convenience was to consider decreasing number of trips through the chute by administration of two doses of PGF2α concurrently with CIDR removal. More recent work in heifers indicated that a single dose of PGF2α at CIDR removal was adequate to induce luteolysis in both diary (Rabaglino et al, 2010) and beef heifers (Cruppe et al, 2014;Kasimanickam et al, 2014 More recently discussion has focused on the requirement or need for GnRH on the front end on the 5dCO. The fact remains that any estrous synchronization protocol that uses GnRH on the onset of the protocol, such as the 5dCO, only 66 to 70% of beef cows have been shown to respond to the initial injection of GnRH (Geary et al, 2000).…”
Section: Modificationsmentioning
confidence: 99%
See 1 more Smart Citation